Mapping of Dengue Fever Distribution based on Indonesian National Standard Cartography Rules as an Prevention Indicator of Outbreaks (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
The purpose of the study was to know the relationship of population density with DHF cases and determine the fluctuation in dengue fever cases in the Hulu Sungai Selatan Regency in 2008-2014. The population in this study was all DHF cases had recorded by the Public Health Office of Hulu Sungai Selatan Regency in 2014-2018, obtained from DHF cases data and population density data. The data were analyzed using spatial analysis with ArcGIS and linear correlation analysis. The results showed the highest average DHF cases is in Kandangan Subdistrict with 471 cases in 2014-2018. The study showed the relation betweenDHF cases with population density was DHF cases (r) is 0.891, while the Sig. (2-tailed) 0.05, so the incidence of DHF cases is significant. Spatial analysis showed that the highest DHF cases happened in the area with a high population density. The use of Geographic Information Systems is expected to facilitate government in reduce cases of DHF in Hulu Sungai Selatan Regency. The preventions that can be made are eradication of mosquito nests, periodic larvae checks, and health education so that dengue fever cases can decrease especially in densely populated areas and special education for DHF in schools. This research also can be used as a reference for better regular preventive counseling models by health workers in communities such as government agencies, regional residents and schools.